Loss of the virulence plasmid by Shigella sonnei promotes its interactions with CD207 and CD209 receptors. Issue 3 (16th March 2021) - Wu, Bi-cong; Olivia, Njiri A.; Tembo, John Mambwe; He, Ying-xia; Zhang, Ying-miao; Xue, Ying; Ye, Cheng-lin; Lv, Yin; Li, Wen-jin; Jiang, Ling-Yu; Huo, Xi-xiang; Sun, Zi-yong; et al.
Abstract : Introduction. Shigella sonnei, the cause of bacillary dysentery, belongs to Gram-negative enteropathogenic bacteria. S. sonnei contains a 210 kb virulence plasmid that encodes an O-antigen gene cluster of LPSs. However, this virulence plasmid is frequently lost during replication. It is well-documented that after losing the O-antigen and becoming rough strains, the Gram-negative bacteria may express an LPS core on its surface. Previous studies have suggested that by using the LPS core, Gram-negative bacteria can interact with several C-type lectin receptors that are expressed on antigen-presenting cells (APCs). Hypothesis/Gap Statement. S. sonnei by losing the virulence plasmid may hijack APCs via the interactions of LPS-CD209/CD207. Aim. This study aimed to investigate if the S. sonnei rough strain, by losing the virulence plasmid, interacted with APCs that express C-type lectins of human CD207, human CD209a and mouse CD209b. Methodology. SDS-PAGE silver staining was used to examine the O-antigen expression of S. sonnei WT and its rough strain. Invasion assays and inhibition assays were used to examine the ability of S. sonnei WT and its rough strain to invade APCs and investigate whether CD209 and CD207 are receptors for phagocytosis of rough S. sonnei . Animal assays were used to observe the dissemination of S. sonnei . Results. S. sonnei did not express O-antigens after losing the virulence plasmid. The S. sonnei rough strain invades with APCs, including human dendritic cells (DCs) and mouse macrophages. CD209 and CD207 are receptors for phagocytosis of rough S. sonnei . Expression of the O-antigen reduces the ability of the S. sonnei rough strain to be disseminated to mesenteric lymph nodes and spleens. Conclusion. This work demonstrated that S. sonnei rough strains – by losing the virulence plasmid – invaded APCs through interactions with CD209 and CD207 receptors.